No Effect of Acute Eccentric Resistance Exercise on Immune Responses to Influenza Vaccination in Older Adults: A Randomized Control Trial - Elzayat, Mahmoud T.; Markofski, Melissa M.; Simpson, Richard J.; Laughlin, Mitzi; LaVoy, Emily C. (Frontiers in Physiology, 2021)
Introduction Older adults are at elevated risk for morbidity and mortality caused by influenza. Vaccination is the primary means of prophylaxis, but protection is often compromised in older adults. As resistance exercise mobilizes immune cells into muscle, it may enhance vaccination response. Purpose Compare antibody and cell mediated immune responses to influenza vaccination in older adults who performed eccentric resistance exercise immediately prior to vaccination to those who did not exercise. Methods Twenty nine resistance training-naive older adults (20 women, 73.9 ± 5.3 years) were randomized to 1 of 3 groups: vaccination in the same arm that exercised (Ex-S), vaccination in the opposite arm that exercised (Ex-Op), and seated rest (No-Ex). Exercise consisted of 10 sets of 5 eccentric unilateral repetitions at 80% of the pre-determined concentric one repetition maximum. Lateral raises were alternated with bicep curls. No-Ex sat quietly for 25 min. Following exercise or rest, all received the 2018 quadrivalent influenza vaccine (Seqirus Afluria) in the non-dominant deltoid. Antibody titers against each influenza vaccine strain were determined by hemagglutinin inhibition assays at baseline, 6-, and 24-weeks post-vaccination. Influenza-specific T cells were quantified after stimulation with the vaccine by intracellular cytokine staining. Results No significant group x time effects were found in antibody responses to any strain (interaction for A/H1N1: p = 0.682; A/H3N2: p = 0.644; B/Colorado/06/2017: p = 0.262; B/Phuket/3073/2013: p = 0.851). Groups did not differ in fold-increase of antibody titers 6- and 24-weeks post-vaccination. Influenza-specific T-cells did not differ between groups at any time (comparison at baseline: p = 0.985; 6-weeks: p = 0.889; 24 weeks: p = 0.857). One subject (Ex-S) reported flu-like symptoms 18 weeks post-vaccination. Conclusion Acute arm eccentric exercise did not influence antibody titers or cell mediated immune responses to the influenza vaccine delivered post-exercise in older adults. More strenuous exercise may be required for exercise to act as an adjuvant. ClinicalTrials.gov Identifier: NCT03736759.